Excessive Screen Time and Its Emerging Health Hazards in Children of Female Health Care Professionals: A Descriptive Cross-Sectional Study: Screen Time and Health Risks in Children of Female Health Professionals - Zubair, Fatima; Chaudhry, Ashraf; Arshad, Fatima; Ain, Qurat Ul; Fatima, Iqra; Amin, Bushra; Kazmi, Tahseen (Pakistan Journal of Health Sciences, 2025)
Excessive screen time is a growing concern, particularly among children of working parents, including female health professionals. While digital devices are often used as convenient tools to manage childcare amidst demanding schedules, prolonged exposure poses risks to physical, cognitive, and emotional health. Objectives: To determine the prevalence and health hazards of excessive screen time in children of female health professionals. Methods: This descriptive cross-sectional study was conducted over six months, from January 2025 to July 2025, at the Combined Military Hospital, Lahore, Pakistan. A total of 195 children aged 4–15 years were included. Excessive screen time was defined as more than 2 hours per day. Data were collected using a validated questionnaire, and statistical analysis was performed using the chi-square test to determine associations, with a p-value <0.05 considered statistically significant. Results: Of the participants, 44.6% were obese, 47.7% had behavioral problems, 53.8% showed speech delays, and 49.2% reported sleep disturbances. Musculoskeletal pain (46.7%) and eye strain (44.6%) were also common. Excessive screen use was significantly associated with sleep and developmental delays. Chi-square test showed significant associations with behavioral issues and education level. Conclusions: Excessive screen time poses multiple health risks in children of female health professionals. Interventions through parental education, ergonomic guidance, and policy measures are needed to reduce these hazards.